Mechanical behaviour of natural turf sports surfaces - Caple, Matt C. J. (Cranfield University, 2011)
The understanding of the mechanical behaviour of natural turf pitches is limited, owed in part to the deficiencies in current testing devices and methodologies. This research aimed to advance the understanding of surface mechanical behaviour through in-situ and laboratory experiments, and via the development of new testing devices. An impact testing device, the Dynamic Surface Tester (DST) was developed, with impacts replicating the magnitude of stress applied by athletes onto turfed surfaces during running. Developmental experiments indicated that the device was sensitive to changes in soil condition due to variations (P<0.05) in impact data. Cont/d.